2010
DOI: 10.1007/s10597-010-9320-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Utilization Among Patients with Severe Mental Disorders

Abstract: In light of healthcare reforms, the study aims to assess variables associated with mental healthcare service utilization in general and in both primary and specialized care by patients with severe mental disorders (SMD, mainly schizophrenia). The study is based on a sample of 140 patients with SMD from five regions in Quebec (Canada). Variables were organized in accordance with Andersen's conceptual model into four factors: predisposing, enabling, needs, and service utilization. Secondary analyses were also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(61 reference statements)
1
5
0
1
Order By: Relevance
“…These findings are in line with other studies on psychiatric services2,12,13 and do not come as a surprise since 75% of patients with schizophrenic disorders have relapses and continued disability, and one-third fail to respond to standard treatment 14…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with other studies on psychiatric services2,12,13 and do not come as a surprise since 75% of patients with schizophrenic disorders have relapses and continued disability, and one-third fail to respond to standard treatment 14…”
Section: Discussionsupporting
confidence: 91%
“…Despite the pervasive need for mental health treatment among individuals with mental disorders, it is generally acknowledged that a great proportion of them do not use healthcare services [ 15 , 16 , 17 , 18 , 19 ]. Canadian studies report that less than 40% of Canadians suffering from mental disorders consult a healthcare professional or services for mental health reasons [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decision to seek help for mental disorders is a complex process that involves personal socio-demographic characteristics, culturally mediated interpretations of symptoms, availability of healthcare services, economic and socio-structural factors, and healthcare service organization [ 22 ]. A number of healthcare service utilization models exist [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ], but most studies of healthcare service utilization for mental health reasons have used the behavioral model developed by Andersen in the 1960s [ 15 , 16 , 17 , 18 , 30 , 31 , 32 ]. This model conceptualized healthcare service utilization as a function of individuals’ predisposing, enabling, and needs characteristics [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our research, few general practitioners managed patients with serious mental disorder on a consistent basis. A parallel random cohort study of 140 patients with serious mental disorder released from hospital 12 months before the survey and living in five of Quebec's administrative health regions (Fleury et al, 2010b) showed that 93% of patients were followed by a psychiatrist, 84% by a case manager, and only 50% by a general practitioner. There are many reasons explaining why only a minority of general practitioners manage patients with severe mental disorder.…”
Section: Discussionmentioning
confidence: 99%